2005
DOI: 10.1016/j.femsle.2005.04.031
|View full text |Cite
|
Sign up to set email alerts
|

The putative chitin deacetylase ofEncephalitozoon cuniculi: A surface protein implicated in microsporidian spore-wall formation

Abstract: Microsporidia are fungal-like unicellular eukaryotes which develop as obligate intracellular parasites. They differentiate into resistant spores that are protected by a thick cell wall composed of glycoproteins and chitin. Despite an extensive description of the fibrillar structure of this wall, very little is known about its protein components and deposit mechanisms. In this study on the human pathogen Encephalitozoon cuniculi, we identify by mass spectrometry the target of polyclonal antibodies previously ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 44 publications
0
53
0
Order By: Relevance
“…However, few studies have reported on the interactions between spore wall proteins (SWPs) and the DCSCs in microsporidia. At present, several spore wall proteins that are localized to the exospore or endospore have been identified in the genus Encephalitozoonidae (14,(16)(17)(18)(19)(20). For N. bombycis, only two exosporal proteins (21-23), three endosporal proteins (21,24,25), and a BAR-2 spore wall protein (26) have been characterized.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies have reported on the interactions between spore wall proteins (SWPs) and the DCSCs in microsporidia. At present, several spore wall proteins that are localized to the exospore or endospore have been identified in the genus Encephalitozoonidae (14,(16)(17)(18)(19)(20). For N. bombycis, only two exosporal proteins (21-23), three endosporal proteins (21,24,25), and a BAR-2 spore wall protein (26) have been characterized.…”
mentioning
confidence: 99%
“…Although chitin is the major component of the spore wall, only one chitin-associated protein has been identified. The chitin deacetylase activity of E. cuniculi (EcCDA) has been confirmed to be expressed during sporogonic stages (14). Currently, the deproteinated chitin spore coats (DCSCs) of the N. bombycis endospore are isolated using a heated alkali solution (15).…”
mentioning
confidence: 99%
“…However, little is currently known about the components of the spore wall. Only seven spore wall proteins in E. cuniculi and E. intestinalis were identified by monoclonal or polyclonal antibodies (Bohne et al, 2000;Brosson et al, 2005;Peuvel-Fanget et al, 2006;Southern et al, 2007;Xu et al, 2006;Hayman et al, 2001). Among fourteen hypothetical spore wall proteins from N. Bombycis deposited in GenBank data, only five complete spore wall proteins have been identified, which contain two endosporal proteins(SWP25 and SWP30) and three exosporal proteins (NbSWP5, SWP26, and SWP32) (Wu et al, 2008;Wu et al, 2009;Li et al, 2009;Cai et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a total of seven spore wall proteins have been reported in E. cuniculi (Bohne et al, 2000;Brosson et al, 2005;Peuvel-Fanget et al, 2006;Southern et al, 2007;Xu et al, 2006) and Encephalitozoon intestinalis (Southern et al, 2007;Hayman et al, 2001), and four spore wall proteins from N. bombycis including SWP25, SWP30, SWP26 and SWP32 were addressed on the location and function (Wu et al, 2008;Li et al, 2009). In our previous study, we identified an exosporal protein NbSWP5 that can protect spores from phagocytic uptaking by cultured insect cells (Cai et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…EnP1 was later localized to the exospore as well and found to mediate adherence to host cells (36). Similar techniques were used to localize a putative chitin deacetylase to the E. cuniculi plasma membrane-endospore interface, suggesting a role in microsporidian endospore development (6).…”
mentioning
confidence: 96%